Hip Abductor Strength Asymmetry: Relationship to Upper Extremity Injury in Professional Baseball Players. (March 2023) - Plummer, Hillary A.; Cai, Zhongjie; Dove, Hannah; Hostetter, Geoff; Brice, Thomas; Chien, Audrey; Sum, Jonathan C.; Hawkins, Andrew; Li, Bernard; Michener, Lori A.
Background: Hip strength is an important factor for control of the lumbo-pelvic-hip complex. Deficits in hip strength may affect throwing performance and contribute to upper extremity injuries. Hypothesis: Deficits in hip abduction isometric strength would be greater in those who sustained an upper extremity injury and hip strength would predict injury incidence. Study Design: Prospective cohort study. Level of Evidence: Level 3. Methods: Minor League baseball players (n = 188, age = 21.5 ± 2.2 years; n = 98 pitchers; n = 90 position players) volunteered. Hip abduction isometric strength was assessed bilaterally with a handheld dynamometer in side-lying position, expressed as torque using leg length (N·m). Hip abduction strength asymmetry was represented by [(trail leg/lead leg) × 100]. Overuse or nontraumatic throwing arm injuries were prospectively tracked. Poisson regression models were used to estimate relative risk ratios associated with hip asymmetry; confounders, including history of prior overuse injury in the past year, were included. Results: Hip abduction asymmetry ranged from 0.05% to 57.5%. During the first 2 months of the season, 18 players (n = 12 pitchers) sustained an upper extremity injury. In pitchers, for every 5% increase in hip abduction asymmetry, there was a 1.24 increased risk of sustaining a shoulder or elbow injury. No relationship between hip abduction strength and injury was observed for position players. Conclusion: Hip abduction asymmetry in pitchers was related to subsequent upper extremity injuries. The observed risk ratio indicates that hip abduction asymmetry may contribute a significant but small increased risk of injury. Clinical Relevance: Hip abduction muscle deficits may affect pitching mechanics and increase arm stress. Addressing hip asymmetry deficits that exceed 5% may be beneficial in reducing upper extremity injury rates in pitchers.